M/B : Moscou-Bernadette - Vanbelle, Annelies; S.M.A.K. Gent; NUCLEO, Gent (Gent : Lieven Decaluwe, 2011)
Bart Lodewijks, Frank Depoorter, Bob Vandeputte, Emilio Lopez-Menchero, Stief Desmet, Koen Broucke, Saar De Buyser, Hugo Azcuy Castillo, Anno Dijkstra
Publicatie als laatste cahier in het kader van Moscou-Bernadette te Gent, 15.12.2011
boek